2016
DOI: 10.1038/srep21374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Liver Kinase B1(LKB1) Protein and Gene Expression in Breast Cancer

Abstract: Liver kinase B1 (LKB1) is a tumor suppressor, and its loss might lead to activation of the mammalian target of rapamycin (mTOR) and tumorigenesis. This study aimed to determine the clinical relevance of LKB1 gene and protein expression in breast cancer patients. LKB1 protein expression was evaluated using immunohistochemistry in tumors from early breast cancer patients in two Taiwanese medical centers. Data on LKB1 gene expression were obtained from the Molecular Taxonomy of Breast Cancer International Consort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…The expression of LKB1 in tumours cells was previously reported as 71%, which is slightly lower than the expression reported in our population (78%) [24]. This could be explained by the age of the population, as our study included patients 70 years or older, while the previously reported data included four groups with median ages of 48, 54, 61 and 62 years [24]. In our study, the association between LKB1 positivity and the factors mentioned above suggests its role as a possible poor prognostic indicator.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The expression of LKB1 in tumours cells was previously reported as 71%, which is slightly lower than the expression reported in our population (78%) [24]. This could be explained by the age of the population, as our study included patients 70 years or older, while the previously reported data included four groups with median ages of 48, 54, 61 and 62 years [24]. In our study, the association between LKB1 positivity and the factors mentioned above suggests its role as a possible poor prognostic indicator.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study, the association between LKB1 positivity and the factors mentioned above suggests its role as a possible poor prognostic indicator. The association of LKB1 expression with high histological grade suggests a poor prognostic indication as reported previously, where IHC was used for the detection of LKB1 protein expression [24]. While in vitro studies reported a negative correlation between both LKB1 mutation and grade and VEGF and a positive correlation with hormone receptor expression [1,3,12,25], these studies analysed LKB1 using Western blot and RT-PCR [1,3,11].…”
Section: Discussionmentioning
confidence: 98%
“… 66 Importantly, LKB1 is a tumour suppressor kinase and its loss promotes breast cancer metastasis and invasion. 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“…Of note, it is hard to associate the expression profile of LKB1 with a specific BC subtype, since the cohorts studied give rise to contradictory results. This could be due to the difference in the cohorts' size, the methods used to detect LKB1 (western blot, immunohistochemistry, RT-PCR…) and the fact that LKB1 localization is not always taken into account [14] [72] [78].…”
Section: Lkb1 a Potentiallymentioning
confidence: 99%